Interaction and Communication of Autism Students in SLBN Cileunyi Bandung Regency - Fitria, Sri Rahayu (Dinamika Bahasa dan Budaya, 2024)
Communication and interaction are the most difficult thing for autism. It is hard for them to open conversation and to recognize the situation around them. the most difficult They can't concentrate to the things around them. Just focus to the activity that they have started. Even when we call them it should be more often until they recognize it. They answer without any eye contact. this research describes how the autistic students communicate and interact with their teachers and their friends how the teacher gets engage with them., and this study analysed four children with autism: 14 years old, produce weak sound, he will speak if the teacher call him by focusing his face to the teacher, 9 years old used verbal language, he can hear but can't produce the sound, a boy has unstable emotional sometimes, and tries to get observer attention to his ability. The informants of this research are four teachers of SLBN Cileunyi, Bandung. This research is qualitative research, data collected by observation, interviews and documentation. Analysis of data used reduction of data, representing, conclusion and verification of data. The validity of data used by correlating the data from informants, observing the children behaviour, and the theory. The result of research shows that each of children are in the level of different autism. it is high, average and low. The guidance and full of care and warm heart is the most comfortable intervention for the autism. They brave to talk, to do the instruction, and to give the attention is depends on the approach of the teachers. Keywords: interaction, communication, autism, eye contact, concentrate